The National hunger march, 1931 - Film and Photo League (U.S.); Museum of Modern Art (New York, N.Y.). Circulating Film Library (New York : Museum of Modern Art Film Library, 1982)
Shows the National Unemployment Council Hunger March of Nov. and Dec. 1931, concentrating on the activity as 1,650 men and women, black and white, set out from disparate parts of the U.S. to represent twelve million unemployed.
Editors, Lester Balog, Robert Del Duca, Leo Seltzer.
Keywords: Depressions -- 1929 -- United States; Demonstrations -- United States; United States -- History -- 1919-1933.